Asian stock markets and the Severe Acute Respiratory Syndrome (SARS) epidemic: implications for health risk management. (7th May 2010) - Bhuyan, Rafiqul; Lin, Eric C.; Ricci, Paolo F.
Time series statistical methods are used to study the financial impact of the Severe Acute Respiratory Syndrome (SARS) epidemic via the co-integration (interdependence) of time series of indexes of several Asian stock markets. We find that during and after the SARS influenza crisis, stock market returns of the infected countries exhibited significant increase in co-integrated relationship and dynamic co-movements, compared to the pre-SARS period. We also find that the effect of the SARS outbreak extended well beyond the Greater China region and influenced most Southeast Asian countries; our empirical results support the notion of 'Globalisation of Commerce and Epidemics'. Furthermore, the findings have several implications for risk managers in the public health sector; we suggest a risk management model for preparing resources against future pandemics of infectious diseases, such as the A-H1N1 influenza.